2022
DOI: 10.18332/tid/146907
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatizing attitudes about lung cancer among individuals who smoke cigarettes

Abstract: INTRODUCTION Many individuals with lung cancer report experiencing stigma associated with their diagnosis. The objective of this study was to explore how different factors, including smoking status, lung cancer concern, and thoughts on smoking behaviors, were associated with increased stigmatizing attitudes towards people with lung cancer. METHODS In 2015, a Web-based survey was completed by people who currently smoked. Participants (n=1419) aged 18-65 years were randomly assigned to one of three scenarios in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Regarding individuals with health issues, stigma can be defined as a social process marked by exclusion, rejection, blame, or devaluation, it arises from the experience, perception, or anticipation of negative social judgments resulting from a lasting health-related identity [ 18 ]. Within the literature, the stigmatization of individuals with health issues is assessed through various variables including negative attributions and blames towards patients, beliefs about personal responsibility and controllability of behaviors, as well as helping behaviors towards patients [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. The concept of stigma is also intricately linked to that of social support, as it has been demonstrated that social support not only notably mitigates the adverse effects of stigma on the psychological well-being of patients but also contributes to fostering resilience and enhancing physical health, especially in the case of liver cancer [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding individuals with health issues, stigma can be defined as a social process marked by exclusion, rejection, blame, or devaluation, it arises from the experience, perception, or anticipation of negative social judgments resulting from a lasting health-related identity [ 18 ]. Within the literature, the stigmatization of individuals with health issues is assessed through various variables including negative attributions and blames towards patients, beliefs about personal responsibility and controllability of behaviors, as well as helping behaviors towards patients [ [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ]. The concept of stigma is also intricately linked to that of social support, as it has been demonstrated that social support not only notably mitigates the adverse effects of stigma on the psychological well-being of patients but also contributes to fostering resilience and enhancing physical health, especially in the case of liver cancer [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first factor, i.e., the drinking habits, was chosen considering that a former study focused on self-stigma showed there may be differences in stigmatization between individuals who only occasionally use alcohol and those with an alcohol use disorder [ 46 ]. The second factor, i.e., the drinking behavior following cancer diagnosis, was selected based on studies of stigmatizing attitudes regarding fictional patients with lung cancer, as studies showed that patients who smoke were judged more negatively than those who were non-smokers or who quit smoking at the time of diagnosis [ 53 , 54 ]. A third factor was the type of cancer diagnosis and prognosis, as cancer stage has been linked to different levels of psychological distress [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…They certainly had a role in the reduction of smoking prevalence observed in most high-income countries, but they also contributed to the public perception that smoking is the unique cause of lung cancer, and furthermore altered empathy for people living with this disease (McLaughlin-Barrett & Brunelli, 2021; Scharnetzki & Schiller, 2021). Interestingly, a recent study in smokers showed that those with high concern about getting lung cancer were more prone to stigmatize patients when compared with smokers less concerned about having the disease (Diaz et al, 2022).…”
mentioning
confidence: 99%